Persepsi Pemahaman Mahasiswa Terhadap PSAK 103 Akuntansi Salam (Studi Empiris pada Mahasiswa Program Studi Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Bone) - Nurwahidah; Rini Idayanti; Musrini Muis (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to evaluate the perceptions and understanding of students of IAIN Bone's Sharia Accounting Study Program of PSAK 103 Accounting for Salam. This type of research is survey research with a quantitative approach. The study population was students from 2021 to 2023 with a sample of 100 respondents who were taken using purposive sampling technique. Data were obtained through questionnaires distributed online. Data analysis was carried out using validity, reliability, normality, T test, and descriptive statistics using SPSS version 26. The results showed that students have a positive perception of PSAK 103 Accounting for Salam, with a significant influence from internal and external factors. Hypothesis H1 is accepted, that is, Sharia Accounting students of IAIN Bone have a positive perception of PSAK 103 Salam Accounting. Hypothesis H2 is also accepted, which shows that internal and external factors have a significant effect on students' perception and understanding of PSAK 103. This study provides theoretical and practical contributions in understanding Islamic accounting standards, especially PSAK 103. In addition, this study also identifies internal factors, such as academic understanding and learning experience, as well as external factors, such as lecturer support and availability of literature, which contribute to shaping students' perceptions of PSAK 103. These findings emphasize the importance of strengthening the curriculum and more interactive learning methods to optimize students' understanding of Islamic accounting standards